Fragmentation modelling of the 2019 August impact on Jupiter. Issue 4 (27th February 2020) - Sankar, Ramanakumar; Palotai, Csaba; Hueso, Ricardo; Delcroix, Marc; Chappel, Ethan; Sánchez-Lavega, Agustin
Abstract: On 2019 August 7, an impact flash lasting ∼1 s was observed on Jupiter. The video of this event was analysed to obtain the light curve, and determine the energy release and initial mass. We find that the impactor released a total energy of 96–151 kilotons of TNT, corresponding to an initial mass between 190 and 260 metric tonnes with a diameter between 4 and 10 m. We developed a fragmentation model to simulate the atmospheric breakup of the object and reproduce the light curve. We model three different materials: cometary, stony, and metallic at speeds of 60, 65, and 70 km s −1, respectively, to determine the material make-up of the impacting object. The slower cases are best fitted by a strong, metallic object while the faster cases require a weaker material.